Considerations for a Malaysian cradle-to-grave identification proposal - Tee, Elok Robert (Faculty of Computer Science and Information Technology, University of Malaya, 1997)
Presents a model for a Malaysian CGID and broadly reviews its requirements and issues in authentication, data storage, security, authorization, duplication and recovery.